Dialogue Education: A Learning-Centered Pedagogy: - Haase, Daniel (Christian education journal, 2019)
When implemented, Dialogue EducationT offers a system of teaching and learning that moves beyond lecture into interactive engagement. This article highlights some of the principles and practices within this dialogical approach to teaching while also demonstrating the methodological techniques within this system of learning. Attention will be given to the nature of transformational education in light of the following elements: the learner, the community, the content, the context, and the role of the Holy Spirit.